Lesion-Induced Blepharospasm: Epidemiology and Clinical Characteristics - Myller, Elina; Halonen, Rolle; Corp, Daniel T.; Joutsa, Juho (Ubiquity Press, Ltd., 2025)
Background: Lesion-induced blepharospasm is considered rare. However, this information is based on a small number of heterogenous retrospective cohorts without routine neuroimaging.
Objectives: To study the epidemiology and clinical characteristics of lesion-induced blepharospasm.
Methods: Patients with blepharospasm with uncertain etiology prior to brain imaging were systematically searched from the electronic medical records of Turku University Hospital (1996-2022). Clinical information and imaging data were extracted from the patients' records and re-evaluated by the investigators. Etiology of blepharospasm was evaluated by an in-depth review of the clinical information in the context of available literature on lesion-induced dystonias. The prevalence and annual incidence of blepharospasm were calculated based on the annual population count in the area.
Results: The search identified 57 patients, of whom four (7.0%) were considered to have lesion-induced blepharospasm, corresponding to a population-based prevalence of 2.5 per million and annual incidence of 0.3 per million. All patients with lesion-induced blepharospasm had atypical features, which were all significantly more common than in patients with idiopathic blepharospasm (P < 0.05).
Conclusions: Lesion-induced blepharospasm is more common than thought previously. However, all these patients showed atypical features, suggesting that brain imaging in blepharospasm can be limited to patients with atypical features only.
Highlights: This study investigated the epidemiology of lesion-induced blepharospasm by systematically re-evaluating all patients with blepharospasm with uncertain etiology prior to structural brain imaging from a university hospital (1996-2022).Our results show that lesion-induced blepharospasm is more common that thought previously (7.0% of included patients, prevalence 2.5 per million, annual incidence 0.3 per million).All patients with lesion-induced blepharospasm showed clinical features that were considered atypical for idiopathic blepharospasm, indicating that routine brain imaging is not needed in patients with typical symptoms.